2019
DOI: 10.1136/bmjopen-2018-027568
|View full text |Cite
|
Sign up to set email alerts
|

‘At the grass roots level it’s about sitting down and talking’: exploring quality improvement through case studies with high-improving Aboriginal and Torres Strait Islander primary healthcare services

Abstract: ObjectivesImproving the quality of primary care is an important strategy to improve health outcomes. However, responses to continuous quality improvement (CQI) initiatives are variable, likely due in part to a mismatch between interventions and context. This project aimed to understand the successful implementation of CQI initiatives in Aboriginal and Torres Strait Islander health services in Australia through exploring the strategies used by ‘high-improving’ Indigenous primary healthcare (PHC) services.Design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 25 publications
1
34
0
Order By: Relevance
“…Previous research has demonstrated the efficacy of participatory research design frameworks in Aboriginal and Torres Strait Islander health contexts. Such research projects have proven successful because they embrace two-way learning and are adapted to the cultural and historical community setting, increasing chances of uptake [28]. This project will involve the ACCHS research partners and their staff in decision-making processes pertaining to the design and implementation of the study, as well as appointing a project Aboriginal and Torres Strait Islander Reference Group whose members will be Aboriginal and Torres Strait Islander researchers, professionals in the health sector and community members with a background/interest in advocating for Elders, ageing well and cognitive health issues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has demonstrated the efficacy of participatory research design frameworks in Aboriginal and Torres Strait Islander health contexts. Such research projects have proven successful because they embrace two-way learning and are adapted to the cultural and historical community setting, increasing chances of uptake [28]. This project will involve the ACCHS research partners and their staff in decision-making processes pertaining to the design and implementation of the study, as well as appointing a project Aboriginal and Torres Strait Islander Reference Group whose members will be Aboriginal and Torres Strait Islander researchers, professionals in the health sector and community members with a background/interest in advocating for Elders, ageing well and cognitive health issues.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of Indigenous research, a community participatory approach is essential to ensure the community, service providers and stakeholders are involved at all stages enabling successful translation into sustainable outcomes [28]. The CQI "plan, study, do, act" cycle will be utilised in combination with the i-PARIHS framework with the purpose of being a practical and familiar way to engage staff in practice change [29,30].…”
Section: Designmentioning
confidence: 99%
“…Stakeholders reported learning new skills in data analysis and being stimulated by the improvement ideas of others [55, 63]. CQI research in Indigenous PHC indicates that support for pooled knowledge assists engagement in improvement initiatives [21, 64, 65]. It is also recognised that co-production can have subtle impact on research capacity-building and knowledge sharing, as well as demonstrable benefits such as policy and practice [66].…”
Section: Discussionmentioning
confidence: 99%
“…The team also used a participatory method of research that involved researchers working with health centre staff and the Indigenous community to co-create new knowledge on a range of factors that appeared to be associated with CQI success. 13 LFTB aimed to use these learnings to empower Indigenous communities and striving PHC centres to improve their systems and service delivery performance and share those lessons widely, including with policy makers.…”
Section: Introductionmentioning
confidence: 99%